A randomised controlled trial of occupational therapy for people with early rheumatoid arthritis. Issue 1 (12th December 2003) - Hammond, A; Young, A; Kidao, R
Abstract : Background: Occupational therapy (OT) aims at improving performance of daily living tasks, facilitating successful adjustments in lifestyle, and preventing losses of function. Objective: To evaluate the effects of a pragmatic, comprehensive OT programme on self management and health status of people with early rheumatoid arthritis (RA) (<2.5 years). Methods: A randomised, controlled "assessor blinded" trial was conducted with assessments made at entry, 6, 12, and 24 months. Main outcomes were AIMS2: physical function (PF), pain visual analogue scale (VAS), and Arthritis Self-Efficacy Scale (ASES). Results: Groups had similar disease duration (9 months OT (n = 162) v 10 months control (n = 164)). The OT group received 7.57 (SD 3.04) hours of therapy. Self management significantly increased in the OT group. Otherwise, there were no significant differences in any outcome measures, or between groups, by ACR functional class: AIMS2: PF (F = 0.04; p = 0.96); pain VAS (F = 0.29; p = 0.74); total ASES score (F = 0.93; p = 0.39). Conclusions: OT improved self management but not health status in early RA. Functional ability remains reasonably good for many in the first five years, so preventive benefits of self management may not yet be apparent and longer follow up is needed. Although many considered the education and therapy useful, insufficient numbers in the OT group used self management sufficiently to make a difference. Behavioural approaches can improve adherence and, potentially, the long term benefits. Future research should evaluate OT as a complex intervention and develop programmes from a theoretical and evidence base.